Perbandingan TIO Sebelum dan Sesudah Operasi pada Pasien Vitrektomi Berbantuan Triamsinolon dengan dan Tanpa Pembedahan Lensa: Hasil Penelitian - Nursalim, Ade John; Sumual, Vera; Wulur, Ardelia Emily (Cermin Dunia Kedokteran, 2025)
Introduction: This retrospective study evaluates the impact of triamcinolone-assisted vitrectomy on intraocular pressure (IOP) in patients undergoing vitreoretinal surgery, with particular focus on comparing outcomes in patients with and without lens surgery. Methods: Medical records of patients treated at R.D. Kandou Hospital from May 2019 to May 2024 were reviewed, and pre- and postoperative IOP values were analyzed. A total of 35 patients met the inclusion criteria. Results: The results show a significant reduction in IOP at all postoperative intervals, with mean differences of 11.12 mmHg at 1 day, 8.60 mmHg at 1 week, 13.23 mmHg at 1 month, and 16.91 mmHg at 3 months postoperatively. Analysis revealed no significant difference in IOP outcomes between phakic and pseudophakic patients. Conclusion: These findings indicate that triamcinolone-assisted vitrectomy effectively lowers IOP, regardless of lens status.